Are Wolf-Rayet Stars Able to Pollute the Interstellar Medium of Galaxies? Results from Integral Field Spectroscopy - Enrique Pérez-Montero; Carolina Kehrig; Jarle Brinchmann; José M. Vílchez; Daniel Kunth; Florence Durret (Advances in Astronomy)
We investigate the spatial distribution of chemical abundances in a sample of low metallicity Wolf-Rayet (WR) galaxies selected from the SDSS. We used the integral field spectroscopy technique in the optical spectral range (3700 Å–6850 Å) with PMAS attached to the CAHA 3.5 m telescope. Our statistical analysis of the spatial distributions of O/H and N/O, as derived using the direct method or strong-line parameters consistent with it, indicates that metallicity is homogeneous in five out of the six analysed objects in scales of the order of several kpc. Only in the object WR404 is a gradient of metallicity found in the direction of the low surface brightness tail. In contrast, we found an overabundance of N/O in spatial scales of the order of hundreds of pc associated with or close to the positions of the WR stars in 4 out of the 6 galaxies. We exclude possible hydrodynamical causes, such as the metal-poor gas inflow, for this local pollution by means of the analysis of the mass-metallicity relation (MZR) and mass-nitrogen-to-oxygen relation (MNOR) for the WR galaxies catalogued in the SDSS.